2002
DOI: 10.1021/jf011563c
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Lignin in the Presence of Tetramethylammonium Hydroxide (TMAH):  Products Stemming from β-5 Substructures

Abstract: Lignin model compounds, synthetic lignins, and cedar wood have been analyzed by pyrolysis-gas chromatography(-mass spectrometry) in the presence of tetramethylammonium hydroxide (TMAH) to examine the behavior of beta-5 substructures specifically under these conditions. Two model compounds contained a beta-5 linkage and a gamma-CH2OH group. The phenolic model compound produced stilbene products by way of a formaldehyde elimination of the gamma-CH2OH. The nonphenolic model compound underwent dehydration to give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…2a shows the TMAH thermochemolysis-GC/MS trace of 1, which mimics a b-5 subunit linked to the edge of the lignin polymer via the phenolic hydroxyl group by b-O-4 linkages cleavable with TMAH. As reported previously[16], alcohol 1 predominantly provided three 2,3,3 0 ,4 0 -tetramethoxy-5-(3-methoxyprop-1-enyl)stilbene isomers (7a-c) in $5:3:10 GC/MS signal area ratio (order of GC/MS elution). TMAH thermochemolysis opened the hydrofuran ring of 1 and successively removed the g-CH 2 OH substituent to produce stilbene 7 lacking substituents at the a-and b-positions, after methylation of the original and new phenolic hydroxyl groups and the B-CH5 5CHCH 2 OH substituent; the intense m/z 71 ion…”
supporting
confidence: 72%
See 2 more Smart Citations
“…2a shows the TMAH thermochemolysis-GC/MS trace of 1, which mimics a b-5 subunit linked to the edge of the lignin polymer via the phenolic hydroxyl group by b-O-4 linkages cleavable with TMAH. As reported previously[16], alcohol 1 predominantly provided three 2,3,3 0 ,4 0 -tetramethoxy-5-(3-methoxyprop-1-enyl)stilbene isomers (7a-c) in $5:3:10 GC/MS signal area ratio (order of GC/MS elution). TMAH thermochemolysis opened the hydrofuran ring of 1 and successively removed the g-CH 2 OH substituent to produce stilbene 7 lacking substituents at the a-and b-positions, after methylation of the original and new phenolic hydroxyl groups and the B-CH5 5CHCH 2 OH substituent; the intense m/z 71 ion…”
supporting
confidence: 72%
“…The previous report [16] with dehydrodiconiferyl alcohol (1) and its methyl ether (1m), 2-arylcoumarans related to softwood b-5 subunits, showed that alcohol 1 provides stilbene 7 isomers (see Fig. 1) and 1m provides benzofuran isomers in TMAH thermochemolysis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kuroda et al [80][81][82][83][84][85] applied thermochemolysis-TMAH to investigate comprehensively the lignin structural network based on the unique chemical bonds between subunits. A study on ␤-5 subunit behavior of lignin model compounds showed that synthetic lignins contain high amounts of terminal ␤-5 substructures while cedar softwood lignin has only small amounts of the terminal ␤-5 substructures [83]. A study on thermochemolysis-TMAH of softwood lignin suggested that 1-(3,4-dimethoxyphenyl)-2-methoxyethene and 1-(3,4-dimethoxyphenyl)-1,2,3,-trimethoxypropane are produced from ␤-aryl ether subunits [84].…”
Section: Ligninmentioning
confidence: 99%
“…Our results [14][15][16] on TMAH thermochemolytic behavior of b-5 and b-b subunits, and 4-O-linked cinnamyl alcohols showed that these do not provide I and II; their TMAH thermochemolysis products are shown in Fig. 3.…”
Section: Introductionmentioning
confidence: 59%